Learning and training on the use of prescribed burning techniques - Colaço, M. C. (2020)
Many of the technicians who applied the technique of prescribed burning were forest and range managers, but they could also be fire fighters, among many other professions. We will use the term fire professional for all of those trained in fire. In our point of view, agreeing with Kobziar et al. (2009), fire professionals should have not only specific training on prescribed burning (professional/continuous training) and practical experience in the field, but also a good fire education (university courses). Following this premise, the objectives of this chapter are to: • Describe and assess the current context on prescribed burning training in Europe (Spain, Portugal and France); • Propose ways to continue the efforts to harmonise qualifications in Europe and to permanently exchange experiences on prescribed training; • Describe and assess the current situation with regard to forest education, university level in Europe (Spain and Portugal) and compare it to the US forest education; • Propose new ways for the example of an International Graduate Program in Fire Science and Management http://www.efi.int/files/attachments/publications/efi_rr23.pdf